Chemical oxidants for remediation of contaminated soil and water. A review - Karpenko, Olexandr; Lubenets, Vira; Karpenko, Elena; Novikov, Volodymyr (Publishing House of Lviv Polytechnic National University, 2009)
This review covers the main agents used for in situ and ex situ chemical oxidation of organic contaminants particularly oil products, in soil and water environments. Among them there are hydrogen peroxide, permanganate salts, ozone and sodium persulfate. The fields of application, as well as benefits and disadvantages of the mentioned agents use were described. Цей огляд присвячений основним реагентам, що використовуються у хімічному окисненні органічних забрудників in citu (безпосередньо на об'єкті) та ex situ (локалізовано), у першу чергу нафтопродуктів, у грунті ті водних ресурсах. Серед них - пероксид водню, перманганати, озон і персульфат натрію. Розглянуто області застосування, а також переваги і недоліки використання зазначених реагентів.
Хімічні окисники для очищення забруднених грунтів і води. Огляд
Keywords: oxidation; remediation; soil; water; contamitants; окиснення; очищення; грунт; водні ресурси; забрудники